2022
DOI: 10.3390/brainsci12030331
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Sleep Structure Assessed in Polysomnography and Right Ventricular Strain Parameters

Abstract: Our study aimed to assess functional, structural changes of the right ventricular using strain parameters and sleep structure using polysomnography in patients with obstructive sleep apnea (OSA). Our study group consisted of 43 patients, 29 men, 14 women. The mean age was 56.36 ± 14.77. All patients underwent full night polysomnography and transthoracic echocardiography. The right ventricular global longitudinal strain was measured by 2D speckle-tracking echocardiography. The prevalence of OSA (AHI ≥ 5) was 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Our meta-analysis showed that TAPSE was reduced in OSA patients compared with controls, but this parameter was not able to differentiate the progressive stages of OSA syndrome. It should be pointed out, however, that the majority of studies included in this meta-analysis failed to find any difference in TAPSE, s' or fractional area change (FAC) between OSA patients and controls [22][23][24][25][26][27][28] and only Altekin and coworkers found that TAPSE was significantly worsened in patients with moderate and severe OSA compared to controls.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our meta-analysis showed that TAPSE was reduced in OSA patients compared with controls, but this parameter was not able to differentiate the progressive stages of OSA syndrome. It should be pointed out, however, that the majority of studies included in this meta-analysis failed to find any difference in TAPSE, s' or fractional area change (FAC) between OSA patients and controls [22][23][24][25][26][27][28] and only Altekin and coworkers found that TAPSE was significantly worsened in patients with moderate and severe OSA compared to controls.…”
Section: Discussionmentioning
confidence: 93%
“…The first literature screening identified a total of 711 papers. After the initial search of titles and abstracts, 661 papers were excluded and 50 were reviewed; of these, eight studies 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 fulfilled the inclusion criteria and comprised sufficient data to be enclosed in the present meta‐analysis (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Investigations mostly agree about reduced RV GLS and free-wall LS in OSA patients [ 13 , 17 , 23 , 26 , 27 , 30 , 31 , 33 ], and most of them speculate about higher sensitivity to recognize subclinical RV damage in patients with preserved parameters of RV systolic function ( Table 2 ). Additionally, authors reported significant difference in RV longitudinal strain values between patients with various OSA severity [ 23 , 30 ], which also contributes to the claims that strain is more sensitive to subtle myocardial changes.…”
Section: Mechanisms Of Rv Remodeling In Osamentioning
confidence: 99%
“…Some authors went so far as to investigate RV segmental changes in OSA patients, and interestingly found no difference in RV basal and apical free-wall LS, even though average free-wall RVLS was significantly lower in OSA patients [ 33 ]. All septal segments showed significantly lower LS in OSA patients, but septum is also part of the left ventricle, and it is difficult to distinguish OSA influence on the left and right ventricle separately.…”
Section: Mechanisms Of Rv Remodeling In Osamentioning
confidence: 99%
See 1 more Smart Citation